2019
DOI: 10.1038/s41598-019-42809-3
|View full text |Cite
|
Sign up to set email alerts
|

Status of Hypertension in Tehran: Potential impact of the ACC/AHA 2017 and JNC7 Guidelines, 2012–2015

Abstract: This study aimed to determine the prevalence of hypertension, the recommended anti-hypertensive therapy and the percentage of hypertensive patients who had achieved the blood pressure (BP) target according to 2017 American College of Cardiology/American Heart Association (ACC/AHA) versus JNC7 and 8 guidelines, among Iranian population. Data of participants aged ≥20 years from the fifth phase (2012–2015) of the Tehran lipid and glucose study (N = 10,576) were analyzed, using survey analysis. The weighted preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
1
24
2
Order By: Relevance
“…20,23,24 Asgari et al reported similar findings and showed that 90% of hypertensive young adults were low risk for CVD. 4 In the present study, the patients classified as stage 1 HTN were about 7 years younger than the stage 2 patients and 3 years younger than the elevated BP patients; they did not show any significant difference with the elevated BP and normal BP groups in the prevalence of the leading risk factors shown in Table 3.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…20,23,24 Asgari et al reported similar findings and showed that 90% of hypertensive young adults were low risk for CVD. 4 In the present study, the patients classified as stage 1 HTN were about 7 years younger than the stage 2 patients and 3 years younger than the elevated BP patients; they did not show any significant difference with the elevated BP and normal BP groups in the prevalence of the leading risk factors shown in Table 3.…”
Section: Discussioncontrasting
confidence: 48%
“…The blood pressure threshold for diagnosis and management of hypertensive patients has decreased dramatically over the past four decades, resulting in a high increase in the prevalence of HTN; eg two to three times in the current study, China, Peru, the USA, Canada, and other studies in Iran, based on the 2017 ACC/AHA guidelines. 4,[19][20][21][22] Defining stage 1 HTN based on the 2017 ACC/AHA guidelines plays the most important role in increasing the prevalence of HTN as well as the proportion of hypertensive young adults. 20,23,24 Asgari et al reported similar findings and showed that 90% of hypertensive young adults were low risk for CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of this increase was not the same among different studies in Iran and other countries. While we reported an increase of over two folds, another study in Iran found an increase of about three folds from 12.6 to 42.7% from the fifth Table 4 Comparison of hypertension associated measures in males and females residents of Yazd Greater area according to JNC7 and ACC/AHA 2017 guidelines 2014-2015 phase (2012-2015) of the Tehran Lipid and Glucose Study [23]. An increase of 1.4 times from 31.9 to 45.6% in United States, [10] 1.6 times from 30.4 to 49.2% in Korea [24] and 1.9 times in Southwest China [25] was seen in different populations across the world.…”
Section: Discussionmentioning
confidence: 80%
“…The authors also found that BP ≥ 130/85 mmHg in the absence of other risk factors was significantly associated with mortality in both genders [ 40 ]. This strong association between high BP and risk of CVD and hard CVD events in our study could be due to the high burden of high blood pressure in the MENA region in the background of the unfavorable trend of obesity, physical inactivity, Westernized diet as well as other psycho-socio-economic factors [ 1 , 41 ]. The 2017 guideline for the high BP of the ACC/AHA [ 30 ], updated the 2003 Seventh Report of the Joint National Committee (JNC7) [ 42 ] and the 2014 eight-panel member report (JNC8) [ 43 ] guideline in terms of the new definition for hypertension, candidates for pharmacotherapy and blood pressure target goals.…”
Section: Discussionmentioning
confidence: 93%